Development of Monoclonal Hybridoma Cell Lines and Extracting Antibody Against Fummonisin B1 - Guangyu Yang; Wenxue Li; Xiaoyun Liang; Jinyin Wu; Wei Zhu (Journal of Basic & Applied Sciences, 2015)
Objective:To acquire monoclonal hybridoma cell lines against fummonisin B1(FB1) and extract monoclonal antibody against FB1. Methods: Coupling antigens of FB1-KLH and FB1-BSA with chemical methods and immune 6-8 weeks old femaleBALB/c mice with FB1-KLH. Integrating spleen cells with sp2/0 myeloma cells to acquire hybridoma cell lines secreting McAb against FB1. The method of multiple subclones was used to select cell lines stably secreting McAb. McAbs was got from ascites and purified. The subclass of antibody was measured and the molecular weight was identified. The specificity and sensitivity of McAb were identified with indirect competitive inhibition ELISA. Results:The results of serum from immuned mice showed that after five times of immunization the titer stables at 1×10-6, and the McAb belongs to IgG1 subclass, the light chain was ?, the molecular weight of heavy and light chain were 55kDa and 32kDa, respectively. ELISA results showed that McAb could react with FB1. The linear range indirect competitive inhibition ELISA is 10-500ng/ml. Conclusion:The monoclonal hybridoma cell lines and the high specificity,high sensitivity of FB1-McAb was got.